Synthesis, characterization and antimicrobial studies of metal complexes derived from gentamicin sulfate - How, Fiona Ni Foong; Hanapi, Mohammad Faiz Hizzuan; Abang Sapani, Dayang Fatin Nadhirah (Malaysian Institute of Chemistry (also known as Institut Kimia Malaysia), 2021)
The emergence of antimicrobial resistance has reduced the potential of gentamicin, which is a broad-spectrum aminoglycoside antibiotic. Complexation of gentamicin with metal ions is expected to facilitate the antibiotic discovery process and would overcome the antimicrobial resistance. Five metal complexes, Cr(III), Co(II), Ni(II), Cu(II) and Zn(II) complexes from gentamicin sulfate were successfully synthesized and characterized using decomposition point, elemental analyses, IR and UV–Vis spectroscopy. The results showed that all complexes have the general formula of [MLxLy.aH2SO4.bH2O], where M = metal ions (Cr, Co, Ni, Cu or Zn) and Lx = Ly = gentamicin ligand of either L1 = gentamicin C1 (C21H43N5O7) or L2 = gentamicin C2 (C20H41N5O7) or L3 = gentamicin C1a (C19H39N5O7). Characterization showed the presence of sulfuric acid molecules and coordinated water molecules in the metal complexes. Qualitative and quantitative antimicrobial assays were carried out to evaluate the biological activities of the parent compound and its metal complexes. It was found that all the complexes showed antimicrobial activity. The copper complex showed an increase of activity towards all the assayed microbial, while the chromium complex showed an enhanced activity with selectivity towards S. pyogenes and K. pneumonia.